The Role and Mechanism of Retinol and Its Transformation Product, Retinoic Acid, in Modulating Oxidative Stress-Induced Damage to the Duck Intestinal Epithelial Barrier In Vitro - Li Zhang; Rui Tang; Yan Wu; Zhenhua Liang; Jingbo Liu; Jinsong Pi; Hao Zhang (Animals, 2023)
This study aimed to investigate the effects and mechanisms of retinol and retinoic acid on primary duck intestinal epithelial cells under oxidative stress induced by H2O2. Different ratios of retinol and retinoic acid were used for treatment. The study evaluated the cell morphology, viability, antioxidative capacity, and barrier function of cells. The expression of genes related to oxidative stress and the intestinal barrier was analyzed. The main findings demonstrated that the treated duck intestinal epithelial cells exhibited increased viability, increased antioxidative capacity, and improved intestinal barrier function compared to the control group. High retinoic acid treatment improved viability and gene expression, while high retinol increased antioxidative indicators and promoted intestinal barrier repair. Transcriptome analysis revealed the effects of treatments on cytokine interactions, retinol metabolism, PPAR signaling, and cell adhesion. In conclusion, this study highlights the potential of retinol and retinoic acid in protecting and improving intestinal cell health under oxidative stress, providing valuable insights for future research.